(untitled) (Sustainability in Debate, 2014)
The population growth, the rural exodus, the industrialization of consumer goods, and the increase of income generate serious problems of garbage accumulation in the cities. We intend in this study to identify the perception of the population of Rondonopolis (MT) about the challenges and environmental benefits associated to selective collection. For this reason, was use a methodological approach, both exploratory and descriptive. In this survey, we have applied a questionnaire with a random and representative sample of the local’s residents. The results show that the practice of separation of recyclable solid waste in their homes is a great attitude and a change in behavior that influences the formation of conscious citizens in the direction of the preservation of the environment. Furthermore, we did not perceived difficulties to be overcome in the implementation of selective garbage collection in this city because there is already an awareness of environmental preservation by its residents.